Molecular architecture of bacterial amyloids in Bacillus biofilms. Issue 11 (5th August 2019) - Mammeri, Nadia El; Hierrezuelo, Jesus; Tolchard, James; Cámara‐Almirón, Jesús; Caro‐Astorga, Joaquín; Álvarez‐Mena, Ana; Dutour, Antoine; Berbon, Melanie; Shenoy, Jayakrishna; Morvan, Estelle; Grélard, Axelle; Kauffmann, Brice; et al.
Abstract : The formation of biofilms provides structural and adaptive bacterial response to the environment. In Bacillus species, the biofilm extracellular matrix is composed of exopolysaccharides, hydrophobins, and several functional amyloid proteins. We report, using multiscale approaches such as solid‐state NMR (SSNMR), electron microscopy, X‐ray diffraction, dynamic light scattering, attenuated total reflection Fourier transform infrared (FTIR), and immune‐gold labeling, the molecular architecture of B. subtilis and pathogenic B. cereus functional amyloids. SSNMR data reveal that the major amyloid component TasA in its fibrillar amyloid form contain β‐sheet and α‐helical secondary structure, suggesting a nontypical amyloid architecture in B. subtilis. Proteinase K digestion experiments indicate the amyloid moiety is ~100 aa long, and subsequent SSNMR and FTIR signatures for B. subtilis and B. cereus TasA filaments highlight a conserved amyloid fold, albeit with substantial differences in structural polymorphism and secondary structure composition. Structural analysis and coassembly data on the accessory protein TapA in B. subtilis and its counterpart camelysin in B. cereus reveal a catalyzing effect between the functional amyloid proteins and a common structural architecture, suggesting a coassembly in the context of biofilm formation. Our findings highlight nontypical amyloid behavior of these bacterial functional amyloids, underlining structural variations between biofilms even in closely related bacterial species.—El Mammeri, N., Hierrezuelo, J., Tolchard, J., Cámara‐Almirón, J., Caro‐Astorga, J., Álvarez‐Mena, A., Dutour, A., Berbon, M., Shenoy, J., Morvan, E., Grélard, A., Kauffmann, B., Lecomte, S., de Vicente, A., Habenstein, B., Romero, D., Loquet, A. Molecular architecture of bacterial amyloids in Bacillus biofilms. FASEB J. 33, 12146‐12163 (2019). www.fasebj.org